HIV Testing Preferences and Characteristics of Those Who Have Never Tested for HIV in the United States. Issue 3 (2nd March 2023) - Patel, Shilpa N.; Emerson, Brian P.; Pitasi, Marc A.; Tripp, Natalie E.; Marcus, Ruthanne; Delaney, Kevin P.; Chavez, Pollyanna R.
Abstract : A study of characteristics of US adults who had ever and never tested for HIV found that most adults had not been tested for HIV, and most who never tested preferred testing in clinical settings. Abstract : Background: The initial phase of the federal Ending the HIV Epidemic in the U.S. (EHE) initiative prioritized efforts in 57 geographic areas. The US Centers for Disease Control and Prevention recommends persons aged 13 to 64 years be tested for HIV at least once as part of routine health care; however, it is unclear how effectively these testing recommendations have been implemented in EHE priority areas. Methods: In 2021 to 2022, we analyzed data from a Web-based, nationally representative survey of adults fielded in 2021. HIV testing preferences were compared by testing history, demographic characteristics, behaviors, and geography. Results: An estimated 72.5% of US adults had never tested for HIV. Never testing was most prevalent among those aged 18 to 29 or those 50 years or older, non-Hispanic White persons, and those living in the Midwest. Among persons living in EHE priority areas and persons reporting at least one behavior that increases risk of HIV transmission, 69.1% and 48.0%, respectively, had never tested for HIV. The top 3 HIV testing preferences among never testers were as follows: testing for HIV during a routine health care visit (41.2%), testing at an urgent care or walk-in clinic (9.6%), and self-testing (8.1%). Conclusions: Most adults had not been tested for HIV, confirming that US Centers for Disease Control and Prevention recommendations are not being fully implemented, even in EHE priority areas. Moreover, most adults who never tested preferred testing in clinical settings, highlighting missed opportunities. As the EHE initiative continues to advance, it is critical to leverage preferred HIV testing modalities, such as routine testing in clinical settings or HIV self-testing.